OMIP‐088: Twenty‐target imaging mass cytometry panel for major cell populations in mouse formalin fixed paraffin embedded liver. Issue 3 (5th January 2023) - Birrer, Fabienne; Brodie, Tess; Stroka, Deborah
Abstract: The purpose of this 20‐target imaging mass cytometry (IMC) panel is to identify the main cell types in formalin fixed paraffin embedded (FFPE) mouse liver tissue with the Hyperion™ mass cytometer from Standard BioTools (formerly Fluidigm). The antibody panel includes markers to identify hepatocytes (E‐cadherin, HNF4α (hepatocyte nuclear factor 4 alpha), Arginase‐1), liver sinusoidal endothelial cells (LSECs; CD206), Kupffer cells (F4/80, CD206), neutrophils (Ly6G, CD11b), bone marrow derived myeloid cells (BMDMs; CD11b), cholangiocytes (E‐cadherin high), endothelial cells (CD31, α‐SMA), plasmacytoid dendritic cells (CD317), B cells (CD19), T cells (CD3e, CD4, CD8a), NK cells (CD161) as well markers of cell activation (CD44, CD74), proliferation (Ki‐67) and to aid in cell segmentation (Pan‐Actin, E‐cadherin, histone H3). The panel has been tested in other mouse tissues, namely the spleen, colon and lung, and therefore is likely to work across various mouse FFPE samples of interest. It has not been tested using human samples, frozen samples or in suspension mass cytometry because FFPE treatment profoundly changes epitope conformation. In summary, this panel is a powerful tool for pre‐clinical research to determine cellular abundance and spatial distribution within mouse tissues and serves as a scaffold, to which more targets can be added for project specific requirements.